Relationship between cortisol and glucose as physiological stress indicators during growth season in juvenile Siberian sturgeon Acipenser baerii - Eagderi, Soheil; Poorbagher, Hadi; Hasanalipour, Alireza; Çiçek, Erdoğan (Journal of Fisheries, 2020)
The relationship between cortisol and glucose was studied in two-year old farmed Siberian sturgeon Acipenser baerii with a body weight of 340±30 g (mean ± SD) and total length of 45±1 cm from August to November 2017. Thirty-six individuals were randomly selected and stocked in some 3×300 L fiberglass tanks. Blood samples were collected monthly from the tagged fish. The mean cortisol in August, September, October and November were 4.7±0.9, 23.5±3.0, 6.3±0.9 and 7.4±0.9 ng mL–1 respectively whereas glucose concentrations were 44.6±0.4, 27.3±0.6, 49.2±0.7 and 48.5±0.7 mg dL–1 respectively indicating a significant increase in cortisol and decrease in glucose in September, may be due to the exposure to prolonged high temperature (26–28.5°C). Although it was expected to happen naturally due to hyperglycemia of cortisol but no such phenomena was detected. Our results suggest that the consumption of glucose for maintenance of homeostasis and physiological status is a mechanism against the non-optimal thermal regime. This mechanism consumes glucose at a rate higher than that produced by cortisol, causing significant decrease of plasma glucose. In general, there was a reverse relationship between cortisol and glucose concentration during the experiment in Siberian sturgeons.